ANALISIS SISTEM ANTRIAN TERHADAP KEPUASAN NASABAH PADA PT.BANK CENTRAL ASIA TBK KANTOR CABANG AHMAD YANI MAKASSAR - Muh. Rusli Junaid; Firmansyah Firmansyah; Ade Cahyaprandy Saputra (BJRM (Bongaya Journal of Research in Management), 2020)
This study aims to determine whether the queuing system affects customer satisfaction at PT Bank Central Asia Tbk Ahmad Yani Makassar Branch Office. Data collection using primary data obtained from questionnaires using purposive sampling technique. The population is all customers of PT Bank Central Asia Tbk Ahmad Yani Makassar Branch Office totaling 5,970 customers while the sample taken is 100 respondents based on the Slovin formula. The results of the questionnaire have been tested for validity and reliability, as well as tested classic assumptions in the form of assumptions of normality, heteroscedasticity and linearity. Methods of data analysis using simple regression techniques with SPSS 21 program. The results showed that the proposed hypothesis was accepted because it showed positive and significant hypothesis test results. This means that the queuing system has a positive and significant effect on customer satisfaction.